Characterization of a 0.35-Micron-Based Analog MPPT IC at Various Process Corners - Tolentino, Lean Karlo; Cruz, Febus Reidj; Chung, Wen-Yaw (Journal of Telecommunication, Electronic and Computer Engineering (JTEC), 2018)
An analogue maximum power point tracking (MPPT) controller integrated circuit (IC) based on ripple correlation control was modified for low voltage applications in this study to harvest the maximum power from the photovoltaic array or solar panel under partial shading and changes in temperature. The IC was implemented in TSMC 0.35um 2P4M 5V mixed-signal CMOS technology. It was simulated at various process corners namely: typical-typical (TT); slow-slow (SS); fast-fast (FF); slow-fast (SF); and fast-slow (FS). The simulation results showed that at a 400 W/m2 solar irradiance and 25 degrees Celsius temperature, the tracking efficiencies are 99.18%, 98.55%, 98.89%, 98.96%, and 98.90% at different process corners, TT, FF, FS, SF, and SS, respectively.